IMPLEMENTATION OF CAMBRIDGE CURRICULUM IN HISTORY LEARNING IN GRADE XI OF SMA WITAMA PEKANBARU - Annisa Dwi Afika; Bunari; Asril (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to determine the implementation of the Cambridge curriculum in history learning in grade XI of Witama High School in Pekanbaru, the obstacles faced in implementing the Cambridge curriculum in history learning in grade XI of Witama High School in Pekanbaru, and the benefits felt by students from the implementation of the Cambridge curriculum in history learning in grade XI of Witama High School in Pekanbaru. This study used a qualitative method with a case study approach. The data collection methods were observation, interviews, and documentation. The results showed that the implementation consisted of three stages: planning, implementation, and evaluation. There were several obstacles in the implementation, including: the integration of the Cambridge curriculum with the national curriculum, limited class hours, a large amount of subject matter, historical terms in English that were difficult to remember, and students having to adapt to the demands of higher-level thinking. The students' responses regarding the benefits of the policy implementation were: history lessons helped hone their English language skills and increase their vocabulary, helped them think critically and look at history from different perspectives, and increased their knowledge of history.